Lakeshore Christmas - Wiggs, Susan (Don Mills, Ont. : Mira, 2009)
Prim librarian Maureen Davenport lives for Christmas. Finally getting her chance to direct Avalon's annual holiday pageant, she's determined to make it truly spectacular. But it might just require one of those Christmas miracles she's always read about if her co- director-- recovering former child star Eddie Haven--has his way.
Keywords: Christmas pageants -- Fiction; Man-woman relationships -- Fiction; Christmas stories; Love stories